Mapping the edge of the empire: Mayor Francisco Hurtado and the roads and towns of Chiloé - Mansilla-Utchal Almonacid, José (2023)
At the end of the 18th century, some military engineers were assigned to the Chiloé Archipelago to carry out work on fortification works. They were also invested with the hierarchy of Governors or Mayors in charge of the administration, and as such, they were protagonists of a broader horizon of activities, which contemplated taking care of the planning of the territory, its integration through the improvement of existing roads or the construction of new roads, which entailed territorial recognition and mapping. One of these military engineers that stands out is Francisco Hurtado del Pino, author of the three maps that we will expose and that give an account of his work and his days in the Archipelago.